149k views
0 votes
Whats the solution ​

Whats the solution ​-example-1
User Notpeter
by
5.5k points

1 Answer

1 vote

Answer:

Explanation:

To find the center and the radius, we need to put the equation in the (x-a)^2+(y-b)^2=r^2 [a is the x-coordinate, b is the y-coordinate, and r is the radius].

(x+6)^2+(y+7)^2 - 36 - 49 + 69 = 0

(x+6)^2+(y+7)^2 - 16 = 0

(x+6)^2+(y+7)^2 = 16

(x+6)^2+(y+7)^2 = 4^2

The center is (-6,-7) and the radius is 4.

Hope this helps!

User Bryan Butler
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.